ANALISIS PRODUKTIVITAS BAGIAN PEMBUATAN KALSIUM KARBONAT MENGGUNAKAN METODE MARVIN E. MUNDEL DI PT. â€œXZâ€ - Moh. Muhyidin Agus Wibowo; Anggia Kalista; Hendra Suwardana (Prodi Teknik Mesin Universitas Yudharta, 2022)
During this company PT. â€œXZâ€ pay less attention to the efficient use of resources (input) owned both in terms of materials, energy, labor and maintenance of machinery that support the production process, based on the results of surveys and interviews there are some problems that become benchmarks for the background of this research is : first, material: this material is composed of limestone often wet and delay in ordering. Second, electrical energy: This electric energy consists of less efficient electricity usage is the light is often not in the dead time during the day. Third, labor: This workforce consists of less disciplined workforce and less professional workforce. Fourth, machine maintenance: maintenance of this machine consists of less maintenance and old machines. The result of productivity analysis shows that productivity index level of calcium carbonate making section is good. Depreciation productivity index is 105.2, material 107,5, labor 108, energy 102,8, maintenance 150,8, and total productivity 105,1 In addition to increase productivity there are many ways that can be done that raw material should be given cover of asbestos, regular job training, machine scheduling.